The Role of Biogas for Economic Sustainability in Nepal: User’s Perspective - Yadav, Maheshwar Prasad (Journal of Advanced Academic Research, 2017)
Background: Economic sustainability is an important ingredient of sustainable development. Sustainable development is the positive changes in a pattern of resources use in such a way that present needs can be met without destroying the ability for the future generations to meet their needs. Furthermore, renewable energy as an essential ingredient of environment comes from resources which are continually replenished. Renewable energy technologies such as biogas, solar and micro-hydro are widely promoted in Nepal and biogas only considered for this study. Objective: To examine role of biogas for economic sustainability in Nepal based on a case study of Niglihawa VDC of Kapilvastu district. Methodology: This study consists of descriptive cum analytical research design and based on both primary and secondary data. The users’ perspectives of sixteen out of twenty two biogas users have been collected by using structured questionnaire. Moreover, the simple statistical techniques of analysis such as table, percentage, and graphs have been employed in this study. Results: Biogas is an important factor in relation to enterprises and employment through saving time and creating agro-based micro enterprises. Biogas also contributes for economic activities through utilizing bio-slurry as feed and fertilizer. Conclusion: Biogas plays the vital role for the economic sustainability through creating enterprises and employment as well as utilizing bio-slurry as fish meal and fertilizer in the context of Nepal in one way or another. The results may be varied in other area and/or sector of Nepal and beyond.